The application of the self-discrepancy theory in the gender roles domain: Do discrepancies between ideal and actual gender roles explain satisfaction with gender roles? - Jugović, Ivana (Array, 2008)
Higgins’ s theory of self-discrepancy hypothesize that the discrepancy between actual self and ideal self results in dissatisfaction or disappointment. We wanted to examine whether this theory could be applied to gender roles domain. The goal of this study was to examine whether discrepancies between attitudes about gender roles and actual gender roles explain the variance of men and women’ s satisfaction with their gender roles. Participants were 703 women and men from Zagreb (Croatia), age ranging from 20 to 84 years, with parental experiences. Ideal and actual gender roles were measured by the shortened and adapted versions of The Sex Role Egalitarianism Scale that contained 47 items concerning interpersonal relations, education, work, partner relations and parental roles. Multiple regression analyses were computed separately for male and female participants, with the satisfaction with gender roles as a criterion, and socio-economic factors and discrepancies between ideal and actual gender roles as predictors. Results have supported Higgins' theory of self-discrepancy in the domain of gender roles. For women, higher level of education and smaller discrepancy between ideal and actual roles regarding work and parental roles predicted higher satisfaction with gender roles. For men, higher satisfaction was predicted with higher level of education and smaller discrepancy between ideal and actual roles regarding interpersonal relations. The explained variance was significantly bigger for women than for men, probably because the discrepancy between ideal and actual gender roles is larger, and therefore more salient, for women then for men.